2019
DOI: 10.18061/emr.v13i3-4.6572
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Sound Design in a Moving Picture: an Empirical Study with emoTouch for iPad

Abstract: The art of sound design for a moving picture rests basically on the work experience of pragmatists. This study tries to establish some guidelines on sound design: In an experiment 240 participants gave feedback about their emotions while watching two videos, each combined with four different audio tracks – music, sound effects, full sound design (music and sound effects) and no audio (as the comparative "null" version). Each participant viewed an audiovisual combination once to prevent habituation. The lead au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Thinking laterally, interesting analogies can be found in film music research. Studies revealed that music and sound effects influence emotions experienced by the viewer [ 74 ] and enhance immersion and suspense [ 75 ]. Film music furthermore affects the semantic evaluation of film scenes [ 76 ], it can foster empathy with the characters [ 77 ], and the content of film excerpts is remembered more easily when music and pictures convey a congruent mood [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thinking laterally, interesting analogies can be found in film music research. Studies revealed that music and sound effects influence emotions experienced by the viewer [ 74 ] and enhance immersion and suspense [ 75 ]. Film music furthermore affects the semantic evaluation of film scenes [ 76 ], it can foster empathy with the characters [ 77 ], and the content of film excerpts is remembered more easily when music and pictures convey a congruent mood [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from music, sound effects also have an influence on felt emotions and immersion while watching a movie. Kock and Louven (2018) combined silent film scenes with sound effects, music, or sound design (music + sound effects). Two pieces of Modest Mussorgsky's "Pictures at an Exhibition" in the original piano version were used as musical accompaniment.…”
Section: Horror Films and The Potential Impact Of Background Music In...mentioning
confidence: 99%